Diffuse panbronchiolitis in a Samoan man. Issue 3 (7th March 2017) - Gibson, Justine; King, Harrison; Singh, Mahendra; Tran, Khoa
Abstract : Diffuse panbronchiolitis (DPB) is an idiopathic inflammatory disease which is predominantly recognised in the Japanese population with only isolated case reports in Western populations. This is the first reported case of DPB in a Samoan man with typical radiological and histopathological features. He had an excellent response to long‐term erythromycin and this case highlights the importance of recognising this rare disease. Abstract : Diffuse panbronchiolitis (DPB) is an idiopathic inflammatory disease which is predominantly recognised in the Japanese population. This is the first reported case of DPB in a Samoan man with the typical radiological and histopathological features. He had an excellent response to long‐term erythromycin and this case highlights the importance of recognising this rare disease.